2009
DOI: 10.1111/j.1399-0004.2009.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the GNPTAB and GNPTG genes in 13 patients with mucolipidosis type II or type III – identification of eight novel mutations

Abstract: Mucolipidosis II (ML II) and mucolipidosis III (ML III) are diseases in which the activity of the uridine diphosphate (UDP)-N-acetylglucosamine:lysosomal enzyme N-acetylglucosamine-1-phosphotransferase (GlcNAc-phosphotransferase) is absent or reduced, respectively. In the absence of mannose phosphorylation, trafficking of lysosomal hydrolases to the lysosome is impaired. In these diseases, mistargeted lysosomal hydrolases are secreted into the blood, resulting in lysosomal deficiency of many hydrolases and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 18 publications
(49 reference statements)
0
39
0
Order By: Relevance
“…In order to search for the molecular defect(s) underlying the GlcNac-1-phosphotransferase impairment in the patient, cDNA analysis of the GNPTAB transcript was performed and the missense mutation c.1196C>T(p.S399F) [8] was identified in heterozygosity. No other alterations were detected through repeated amplification of the GNPTAB cDNA, even though both the patient clinical presentation and the biochemical results were incoherent with the expectations for a carrier individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to search for the molecular defect(s) underlying the GlcNac-1-phosphotransferase impairment in the patient, cDNA analysis of the GNPTAB transcript was performed and the missense mutation c.1196C>T(p.S399F) [8] was identified in heterozygosity. No other alterations were detected through repeated amplification of the GNPTAB cDNA, even though both the patient clinical presentation and the biochemical results were incoherent with the expectations for a carrier individual.…”
Section: Discussionmentioning
confidence: 99%
“…GNPTAB and GNPTG genomic and cDNA analyses were performed with specific primers according to previously reported conditions [8].…”
Section: Genomic and Cdna Analysismentioning
confidence: 99%
“…We can hypothesise that at least some ML II patients from whom no RNA samples were available and, in whom only one mutant allele has previously been found (Encarnação et al 2009;Tappino et al 2009;Otomo et al 2009;Zarghooni and Dittakavi 2009), might be compound heterozygous for large deletions caused by Alu-mediated mechanisms. The confirmation of that status would be of obvious implications in genetic counselling and prenatal diagnosis, but in which regards to the partially characterised patients from our series (Encarnação et al 2009), RNA samples were available for testing and no gross deletions were found in either of them. Another important point that deserves attention is the fact that patients who have already been classified as homozygous for other GNPTAB mutations may be misclassified if that mutation happens to occur in a region where one of the alleles carries a gross deletion.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular examination of a ML II patient was initially assessed through routine procedures, which involved amplification and direct sequencing of GNPTAB exons and flanking intronic regions (Encarnação et al 2009). However, the failure to amplify the fragment correspondent to exon 19 and its intronic boundaries from the patient's DNA in face of normal amplification from control DNA, led us to suspect that a large deletion could underlie the molecular defect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation